Tinjauan Yuridis Terhadap Klasifikasi Data Pelanggan Perusahaan Listrik Negara (PERSERO) Menurut Perspektif Undang Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi: Penelitian - Raysa Maysa Namiraah; Agus Suprajogi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This journal discusses the classification of PT PLN (Persero) customer data in the context of the tension between personal data protection and public information disclosure, both of which aim to guarantee human rights but can potentially create conflicts of interest in practice. Two research questions are formulated: first, how is PT PLN (Persero) customer data classified based on Law Number 27 of 2022 concerning Personal Data Protection?; and second, how is the synchronization of norms in determining customer data classification according to the Public Information Disclosure Law and Personal Data Protection Law? The research method used is empirical legal research with statutory and sociological approaches, supported by literature studies and in-depth interviews with relevant parties within PT PLN (Persero). The study concludes that the classification of PT PLN (Persero) customer data cannot be done simplistically but must consider the nature of the data, processing purposes, and potential privacy violation risks. The disharmony between the two laws creates legal uncertainty, requiring the application of necessity and proportionality principles as an important basis for balancing public information disclosure and personal data protection interests in customer data management by state-owned enterprises.